An evaluation of the impact of transport infrastructure investment on the economic performance of South Africa - Mogoiwa, Mathapelo Refilwe (University of the Witwatersrand, Johannesburg, 2023)
The decision to invest in economic infrastructure has far-reaching benefits for the South African economy, including innovation, economic growth, job creation, increased productivity, poverty alleviation, and an improvement in the standard of living. Therefore, the current study was conducted to determine the causal impact of selected critical economic variables for positive economic performance. The focus of the study was to evaluate how rail infrastructure investment impacts economic performance by assessing indicators such as economic growth, competitiveness, and unemployment rate using time series data from 1989 to 2018. As a quantitative study, the research employed correlational and causal-effect designs. Quantitative data was collected from credible secondary sources, including the websites and reports of Statistics South Africa, the South African Reserve Bank, the South African Revenue Services, and the World Economic Forum. Data analysis was conducted using descriptive analysis to identify the series of trends In contrast, multivariate time series analysis generated inferential statistics to assess the direction and significance of the relationship between the variables. The study discovered that rail infrastructure investment, competitiveness, and economic growth are significant causal relationships to unemployment and were found to have substantial causal relationships to economic growth. The study findings also confirmed the single-direction hypothesis that rail infrastructure investment Granger causes economic growth, competitiveness, and employment. Bidirectional Granger causal effects were proven between competitiveness and economic growth, competitiveness and unemployment, and economic growth and unemployment
A research report submitted in partial fulfillment of the requirements for the degree of Masters in Management to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2023
Keywords: Rail infrastructure investment; Economic performance; Economic growth; Competitiveness; Unemployment; Vector autoregression; Vector error- correction model; UCTD; SDG-8: Decent work and economic growth